2015
DOI: 10.1055/s-0035-1546824
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging of Peripheral Nerves

Abstract: Diffusion tensor imaging (DTI) is a powerful MR imaging technique that can be used to probe the microstructural environment of highly anisotropic tissues such as peripheral nerves. DTI has been used predominantly in the central nervous system, and its application in the peripheral nervous system does pose some challenges related to imaging artifacts, the small caliber of peripheral nerves, and low water proton density. However advances in MRI hardware and software have made it possible to use the technique in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Imaging artefacts and the small calibre of peripheral nerves hampered its use in the peripheral nervous system. However recent advances in MRI technology have extended its application to the peripheral nervous system[ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Imaging artefacts and the small calibre of peripheral nerves hampered its use in the peripheral nervous system. However recent advances in MRI technology have extended its application to the peripheral nervous system[ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 It recently rose to be a promising method in detecting and monitoring lesions to the peripheral nervous system for its potential to depict the microstructure of nerves. 5,6 Several clinical studies were carried out on the application of DTI in diagnosing NCS, especially the carpal tunnel syndrome (CTS). These studies demonstrated the diagnostic value of the DTI parameters, e.g.…”
mentioning
confidence: 99%
“…DTI has previously been used to detect peripheral nerve regeneration as early as 1–3 months in humans 25‐27 . DTI provides a noninvasive, quantitative approach to evaluate tissue microstructures throughout the recovery process by measuring the diffusion of water molecules in tissue over multiple directions 28 . In the absence of barriers, diffusion is isotropic or equal in all directions.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of barriers, diffusion is isotropic or equal in all directions. Conversely in ordered, elongated biological tissue like axons, water diffusion is anisotropic due to its interactions with surrounding tissue structures and cellular membranes, resulting in an apparent diffusivity that is the highest along the primary direction of the axons 25,28,29 …”
Section: Introductionmentioning
confidence: 99%